Legality of Credit Agreements with Fiduciary Guarantees made with Artificial Intelligence (AI) - Hanim, Lathifah; Rinda Listyawati, Peni; Noorman, MS (Sultan Agung Notary Law Review, 2024)
Fiduciary Guarantee before being used as collateral in a credit agreement, it is mandatory to register the fiduciary first. Electronic fiduciary registration still has problems including network disruptions, system errors and is vulnerable to cyber attacks. Smart contract integration with electronic fiduciary guarantee registration can be a solution to these problems. Smart contract as a form of artificial intelligence / Artificial Intelligence (AI). The purpose of this study is to analyze the legality of credit agreements with fiduciary guarantees made with Artificial Intelligence (AI). The type of research used is empirical legal research, supported by primary and secondary data. The results of the research are that Smart contract is a computer program that can make agreements automatically with the blockchain system.AI is generally viewed as a legal object, not a legal subject. This is because AI is a tool or device used by humans to achieve certain goals. The requirements for the validity of an agreement (including a credit agreement with fiduciary guarantee) remain based on Article 1320 of the Civil Code.